DTV/LTE antennas with no physical structure for laptop computers. Issue 11 (24th July 2021) - Chen, Shu-Chuan; Nieh, Jo-Yen; Liao, Wei-Hsiang; Li, Sheng-Min
Abstract : This paper proposes a DTV/LTE antenna design without physical structure for laptop computers. By changing the laptop's right revolving axis to a non-conductor material and exciting several dipoles and loop paths formed by the display, keyboard ground plane and metal revolving axis using a feed matching circuit at an appropriate position of the slot on the hinge to cover the frequency bands for DTV (470–862 MHz) and LTE (698–960 MHz, 1710–2690 MHz). The feed matching circuit is fitted to the keyboard ground plane adjacent to the hinge. It consists of a 3.6 nH chip inductor and a 0.2 pF chip capacitor to improve the high frequency matching and increase the high frequency bandwidth. The antenna can cover the frequency bands required by DTV and LTE, and the measured antenna efficiency in the operational frequency band is also better than 50%.